“It’s all about the money”: an interpretive description of embedding physical therapy-led falls prevention group exercise in long-term care - Elizabeth Binns; Felicity Bright; John Parsons; Kathy Peri; Lynne Taylor; Ngaire Kerse; Denise Taylor (BMC Geriatrics, 2023)
Abstract Background Falls prevention interventions are effective for community dwelling older adults however, the same cannot be said for older adults living in long-term care (LTC). The Staying UpRight (SUp) randomized controlled trial was designed to test the effectiveness of a progressive strength and balance group exercise program delivered to LTC residents. This paper explores the factors impacting LTC providers’ decisions to continue the program on completion of the funded trial period. Methods A qualitative study using an Interpretive Description approach. Semi-structured interviews and focus groups were conducted with 15 LTC staff involved in the randomized controlled trial. Data were analysed using conventional content analysis. Results Practice change occurred following participation in the trial with some facilities starting exercise groups, some increasing the number of exercise groups offered and physical therapists selecting elements of the program to adopt into their practice. Decisions about continuing with SUp as designed were constrained by organizational decisions regarding funding and resources. Three factors were identified which informed decision-making: business models and philosophies, requirements for evidence, and valuing physical therapy. Conclusions Managers and facilitators adapted SUp by selecting and delivering components of the program in response to the changes they had observed in participating residents. However, our findings highlight that while SUp was valued, the tight financial environment created by the current funding model in New Zealand did not support funding physical therapist delivered falls prevention exercise programs in LTC. This study may provide policy makers with important information on changes needed to support falls prevention service delivery in LTC. Trial registration This study is a sub-study of a randomized controlled trial which was registered to the Australian New Zealand Clinical Trials Registry ACTRN12618001827224 on 09/11/2018. Universal trial number U1111-1217-7148.